EFECT OF SEASONAL VARIATIONS AND WEATHER PARAMETERS ON YIELD, QUALITY AND DISEASE INCIDENCE IN GUAVA CULTIVARS UNDER RAINFED CONDITIONS OF ARS UNDER RAINFED CONDITIONS OF JAMMU REGION - GUPTA, NEERAJ (The Bioscan, 2016)
The six cultivars under the study were Allahabad Safeda, Lucknow-49, Apple Colour, Hybrid 1 and Hybrid 2 and Banarsi Surkha. Lucknow-49 cultivar proved to be most successful variety with the highest fruit yield (78 and 114 kg tree-1) followed by cv. Allahabad Safeda (61 and 88 kg tree-1) in rainy and winter season, respectively. Apple colour cv. recorded lowest (24 kg tree-1) fruit yield during rainy season however cv. Hybrid-2 observed the lowest fruit yield (43 kg tree-1) in winter season. Total soluble solids, total sugars and vitamin C were higher in winter season (14.5 %, 4.82 % and 221 mg 100 g-1) than rainy season crop (10.6 %, 3.33 % and 157 mg 100 g-1), respectively. The minimum disease incidence was recorded in cv. Lucknow-49 (17.7 & 8.0 %) followed by Allahabad Safeda (21.0 & 11.9 %) at harvest in rainy and winter season, respectively. Maximum and minimum temperature, relative humidity (evening) and evaporation were negatively related in rainy season, whereas rainfall was positively related with disease intensity. Hence, it is concluded that winter season guava was more quantitative, qualitative and disease resistant as compared to rainy season crop under rainfed conditions.